A Stable, Autonomously Replicating Plasmid Vector Containing Pichia pastoris Centromeric DNA - Nakamura, Yasuyuki; Nishi, Teruyuki; Noguchi, Risa; Ito, Yoichiro; Watanabe, Toru; Nishiyama, Tozo; Aikawa, Shimpei; Hasunuma, Tomohisa; Ishii, Jun; Okubo, Yuji; Kondo, Akihiko (Applied and environmental microbiology, 2018)
Secretory production of recombinant proteins is the most important application of the methylotrophic yeast Pichia pastoris , a species that permits mass production of heterologous proteins. To date, the genetic engineering of P. pastoris has relied largely on integrative vectors due to the lack of user-friendly tools. Autonomously replicating Pichia plasmids are expected to facilitate genetic manipulation; however, the existing systems, which use autonomously replicating sequences (ARSs) such as the P. pastoris -specific ARS ( PARS1 ), are known to be inherently unstable for plasmid replication and distribution. Recently, the centromeric DNA sequences of P. pastoris were identified in back-to-back studies published by several groups; therefore, a new episomal plasmid vector with centromere DNA as a tool for genetic manipulation of P. pastoris is ready to be developed. The methylotrophic yeast Pichia pastoris is widely used to produce recombinant proteins, taking advantage of this species' high-density cell growth and strong ability to secrete proteins. Circular plasmids containing the P. pastoris -specific autonomously replicating sequence ( PARS1 ) permit transformation of P. pastoris with higher efficiency than obtained following chromosomal integration by linearized DNA. Unfortunately, however, existing autonomously replicating plasmids are known to be inherently unstable. In this study, we used transcriptome sequencing (RNA-seq) data and genome sequence information to independently identify, on each of the four chromosomes, centromeric DNA sequences consisting of long inverted repeat sequences. By examining the chromosome 2 centromeric DNA sequence ( Cen2 ) in detail, we demonstrate that an ∼111-bp region located at one end of the putative centromeric sequence had autonomous replication activity. In addition, the full-length Cen2 sequence, which contains two long inverted repeat sequences and a nonrepetitive central core region, is needed for the accurate replication and distribution of plasmids in P. pastoris . Thus, we constructed a new, stable, autonomously replicating plasmid vector that harbors the entire Cen2 sequence; this episome facilitates genetic manipulation in P. pastoris , providing high transformation efficiency and plasmid stability. IMPORTANCE Secretory production of recombinant proteins is the most important application of the methylotrophic yeast Pichia pastoris , a species that permits mass production of heterologous proteins. To date, the genetic engineering of P. pastoris has relied largely on integrative vectors due to the lack of user-friendly tools. Autonomously replicating Pichia plasmids are expected to facilitate genetic manipulation; however, the existing systems, which use autonomously replicating sequences (ARSs) such as the P. pastoris -specific ARS ( PARS1 ), are known to be inherently unstable for plasmid replication and distribution. Recently, the centromeric DNA sequences of P. pastoris were identified in back-to-back studies published by several groups; therefore, a new episomal plasmid vector with centromere DNA as a tool for genetic manipulation of P. pastoris is ready to be developed.